1988
DOI: 10.1002/eji.1830180405
|View full text |Cite
|
Sign up to set email alerts
|

A cd3 subset of cd48+ thymocytes: a rapidly cycling intermediate in the generation of cd4+8+ cells

Abstract: T lymphocytes with the surface phenotype CD4+8- and CD4-8+ are considered to be representative of functionally mature cells. We show here that adult murine thymus contains a subpopulation of CD4-8+ cells that differ from CD4-8+ cells found in the periphery in that they do not express the T cell receptor-associated CD3 molecular complex. Such CD3-4-8+ thymocytes are cortisone sensitive and rapidly cycling in situ. Furthermore, in contrast to mature T cells, most CD3-4-8+ thymocytes express low levels of CD5 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(81 citation statements)
references
References 27 publications
8
72
1
Order By: Relevance
“…During the DN-to-DP transition, DN4 cells in wild-type mice first differentiate into a proliferative TCRβ lo CD8 ISP stage prior to becoming DP cells (MacDonald et al 1988). Similar to observations in other mutant strains (Harker et al 2002;Naito et al 2007), this TCRβ lo CD8 ISP population was difficult to detect in Ikzf1 ΔF4/ΔF4 mice (Fig.…”
Section: Reduced Double-negative (Dn) Thymocytes In Ikzf1 δF4/δf4 Micesupporting
confidence: 74%
“…During the DN-to-DP transition, DN4 cells in wild-type mice first differentiate into a proliferative TCRβ lo CD8 ISP stage prior to becoming DP cells (MacDonald et al 1988). Similar to observations in other mutant strains (Harker et al 2002;Naito et al 2007), this TCRβ lo CD8 ISP population was difficult to detect in Ikzf1 ΔF4/ΔF4 mice (Fig.…”
Section: Reduced Double-negative (Dn) Thymocytes In Ikzf1 δF4/δf4 Micesupporting
confidence: 74%
“…They emerge after DN cells and before DP cells and are programmed to differentiate into DP cells. These similarities indicate their similar stages of differential pathways from DN to DP cells [14,15,17]. The choice of the "CD8 pathway" or CD4 pathway seems to be genetically destined, with one pathway dominant in one strain of mice [15,16].…”
Section: Discussionmentioning
confidence: 96%
“…Immature CD4 and CD8 single positive (ISP) thymocytes have been recognized and studied intensively during the 1980s and 1990s [12][13][14][15][16]. They have been shown to share great similarities, both being blastic, rapidly cycling, cortisone sensitive, localized in the outer thymic cortex and making up very little proportion in adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…This kinetic pattern contrasts with the behaviors of other three subsets in which a considerable recovery is attained by Day 14. Recent studies have demonstrated that very transient CD3-CD4-CD8+SP cycling cells in the thymus represent an intermediate between DN and DP cells MacDonald et al 1988). So, we must take a possible reduction of this intermediate subset into consideration.…”
Section: Discussionmentioning
confidence: 99%